STUDI PENGARUH PROSES PERENDAMAN DAN PEREBUSAN TERHADAP KANDUNGAN KALSIUM OKSALAT PADA UMBI SENTHE (Alocasia macrorrhiza (L) Schott) - Rizka Amalia; Riris Yuliana Y.S.; Andri Cahyo Kumoro (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2013)
Senthe (Alocasia macrorrhiza (L) Schott) is a kind of tuber that grows widely in the tropical area. Senthe has the potential as a staple food or as a interlude food with a high carbohydrate content. However, senthe contain oxalic acid which can reduce absorption of calcium in the digestive system and calcium oxalate which causes itchiness. The purpose of this research is to investigate the effect of soaking and boiling process toward calcium oxalate and nutritional value in the tuber chips.In this research, the variables are the thickness of slicing (0.5 cm, 1 cm, 1.5 cm), soaking time (2 hours and 4 hours,) weight ratio between tuber and volume of salt soluion (1:3, 1:4, 1:5, 1:6, 1:7) w/v , and the boiling time at (10 min, 20 min and 30 min). Based on research result obtain that the slice thickness 1 cm is the optimum value in the reduction process. While soaking weight ratio and optimum soaking time is at 1:6 (w / v) and 4 hours. Optimum boiling time is 30 minutes. Combination of all treatments can reduce the content of calcium oxalate in senthe of 79.53%. Calcium oxalate reduction in senthe is 351 mg/100g, whereas allowable oxalate levels is 71 mg/100g (Sefa-Dedeh and Agyir-Sackey, 2004), thus,the senthe is still not safe for human consumption.